Direct emergence of the dorsospinal artery from the aorta supplying the anterior spinal artery: report of two cases. - Lefournier, V; Bessou, P; Gailloud, P; Vasdev, A; Rüfenacht, D; Boubagra, K (American Journal of Neuroradiology, 1998)
We report two cases of an isolated dorsospinal artery that emerged directly from the aorta to supply the anterior spinal artery, which in one case had another blood supply on the opposite side, in a lower position. It is important to identify this anatomic variant, otherwise spinal angiography might be incomplete, especially when the isolated dorsospinal artery supplies the anterior spinal artery.